THE INFLUENCE OF DOMESTIC INVESTMENT AND FOREIGN INVESTMENT ON ECONOMIC GROWTH IN INDONESIA - Khairuna Putri; M Rasyidin; M Saleh (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the effect of domestic investment and foreign investment on economic growth in Indonesia. This study uses secondary data using time series data for 30 years from 1994 to 2023. The analysis method used is multiple linear regression. The data used in this study are annual data from each variable sourced from the official website (BPS Indonesia). The results of this study state that domestic investment has no effect on economic growth in Indonesia. And foreign investment also has no effect on economic growth in Indonesia.